2019
DOI: 10.1029/2019jd030727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mesospheric Polar Vortices in WACCM

Abstract: This work evaluates the wintertime mesospheric polar vortices in the Whole Atmosphere Community Climate Model. Mesospheric altitudes are where high‐top models underestimate the concentration of nitrogen oxides produced by energetic particle precipitation. For this reason, we seek to determine the extent to which the observed mesospheric vortex size and frequency of occurrence is reproduced by the model. We compare 13 years (2005–2017) of “specified dynamics” Whole Atmosphere Community Climate Model (where mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 126 publications
(168 reference statements)
4
22
0
Order By: Relevance
“…However, there are important quantitative differences among the DJF zonal mean temperature distributions, most notably in the tropics from 80 to 100 km altitude, where WACCMX+DART produces temperatures that are > 20 K warmer than corresponding temperatures produced by the NAVGEM-HA and JAGUAR-DAS systems. A warm bias at the tropical mesopause has been documented previously in free-running WACCM model simulations (e.g., Smith, 2012;Marsh et al, 2013;Harvey et al, 2019), but the cause is not yet fully understood. We also note that the summer polar temperature at 80 km altitude is ∼ 20 K colder in WACCMX+DART compared to the other three data sets.…”
Section: Zonal Mean Resultsmentioning
confidence: 79%
“…However, there are important quantitative differences among the DJF zonal mean temperature distributions, most notably in the tropics from 80 to 100 km altitude, where WACCMX+DART produces temperatures that are > 20 K warmer than corresponding temperatures produced by the NAVGEM-HA and JAGUAR-DAS systems. A warm bias at the tropical mesopause has been documented previously in free-running WACCM model simulations (e.g., Smith, 2012;Marsh et al, 2013;Harvey et al, 2019), but the cause is not yet fully understood. We also note that the summer polar temperature at 80 km altitude is ∼ 20 K colder in WACCMX+DART compared to the other three data sets.…”
Section: Zonal Mean Resultsmentioning
confidence: 79%
“…km altitude, where WACCMX+DART produces temperatures that are >20 K warmer than corresponding temperatures produced by the NAVGEM-HA and JAGUAR-DAS systems. A warm bias at the tropical mesopause has been previously documented in free-running WACCM model simulations (e.g., Smith, 2012;Marsh et al, 2013;Harvey et al, 2019) but the cause is not yet fully understood. We also note that the summer polar temperature at 80 km altitude is ~20 K colder in WACCMX+DART compared to the other three data sets.…”
Section: Zonal Mean Resultsmentioning
confidence: 98%
“…Westward wintertime winds in the simulated polar MLT are a long-standing feature of WACCM (Harvey et al, 2019;Ramesh et al, 2020;Stober et al, 2021b), and they are also found in the thermospheric extension WACCM-X (Liu et al, 2010;Pedatella et al, 2014;Liu et al, 2018;Pancheva et al, 2020) and in other high-top models such as the MUAM (Lilienthal et al, 2018).…”
Section: Secondary Gws and Differences Between Radar Observations And Waccmmentioning
confidence: 79%
“…This difference is well-known (e.g. Smith, 2012;Harvey et al, 2019) and may be considered as one of the most significant biases in numerical simulations of the MLT with important impacts for MLT chemistry. There is a growing body of literature that suggests that this reversal of the modelled zonal winds could be due to an incomplete representation of drag due to GWs, in particular secondary GWs Becker and Vadas, 2018;.…”
Section: Comparison Of Radar Winds and Satellite Temperatures To Waccmmentioning
confidence: 98%
See 1 more Smart Citation